Leaked (Political) Telephone Conversation in Bangladesh: A Conversation Analysis - Islam , Sadia; Khan, Mahmud Hasan (EAST WEST JOURNAL OF HUMANITIES, 2024)
The paper analyses a selected number of ‘leaked’ telephone conversations by some political figures of Bangladesh. The analyses are rooted in the ideals of conversation analysis (CA), particularly in the CA of telephone interaction. Leaked conversations are politically sensitive, and thus are rarely discussed in the academia. The data for this study is, however, collected from an open source, i.e., YouTube on which the conversations were circulated. The aim of the study is to examine the organizational structure of the telephone conversations carried out by political figures, i.e., political telephone conversation (PTC). The paper explains how individual political actors conduct formal and informal interactions over telephone as they discuss different sensitive issues in relation to politics and society. The paper investigates how the politicians open and close their talk, maintain adjacency pairs, and construct topics as they legitimize their arguments within a conversation. The findings of this paper are expected to contribute to a better understanding of how we can analyze and comprehend the organization of political conversations through the mechanisms of conversation analysis, and at the same time to provide a helpful documentation for further research on this ‘highly neglected’ field.